Top overhauling on Audi – 100 engine / Azlan Abd Ghani, Zurean Azuan Zulkifli and Ismani Zikri Ismail - Abd Ghani, Azlan; Zulkifli, Zurean Azuan; Ismail, Ismani Zikri (Faculty of Mechanical Engineering, 2001)
The Audi - 100 was announced in October 1982 with the Audi - 200 versions becoming available in early 1984. All models features startling new advances in automotive design and technology in its era, foremost among these being the excessive attention to aerodynamics shape with a drag coefficient (Cd) of 0.30 for the Audi - 100, these cars are of a design, which is amongst the most aerodynamically efficient in their class ( See Figure 1.2(a) ).